Targeting Antibiotic Resistance Genes Is a Better Approach to Block Acquisition of Antibiotic Resistance Than Blocking Conjugal Transfer by Recipient Cells: A Genome-Wide Screening in Escherichia coli - Moriguchi, Kazuki; Zoolkefli, Fatin Iffah Rasyiqah Mohamad; Abe, Masanobu; Kiyokawa, Kazuya; Yamamoto, Shinji; Suzuki, Katsunori (Frontiers in Microbiology, 2020)
Conjugal transfer is a major driving force in the spread of antibiotic resistance genes. Nevertheless, no effective approach has been developed to target conjugal transfer to prevent the acquisition of antibiotic resistance by this mechanism. This study aimed to identify potential targets for plasmid transfer blockade, by isolating mutants defective in the completion of the acquisition of antibiotic resistance via conjugal transfer. We performed mutant screening by combining an IncP1-type broad-host-range plasmid conjugation system with a comprehensive collection of Escherichia coli gene knock out mutants (Keio collection; 3884 mutants). No mutants defective in conjugal transfer were isolated, strongly suggesting that E. coli cannot escape from being a recipient organism for P1 plasmid transfer. However, several mutants with a low viability were identified, as well as mutants defective in establishing resistance to chloramphenicol, which was used for transconjugant selection. These results suggest that developing drugs capable of inhibiting the establishment of antibiotic resistance is a better approach than attempting to prevent conjugal transfer to block the spread of antibiotic resistance genes, and our screening system based on the IncP1-type plasmid transfer is applicable to isolation of target genes for the former drugs.